CK2 and protein kinases of the CK1 superfamily as targets for neurodegenerative disorders - Baier, Andrea; Szyszka, Ryszard (Frontiers in Molecular Biosciences, 2022)
Casein kinases represent important therapeutic targets for drug development since they play a central role in a variety of signaling pathways, and also in inflammation, cancer, and neurological diseases. Recent studies have highlighted the importance of the casein kinase 1 superfamily as well as protein kinase CK2 in the development of several neurodegenerative pathologies, such as Alzheimer’s disease, Parkinson’s disease Huntington’s disease, and amyotrophic lateral sclerosis. CK1 kinases and their closely related tau tubulin kinases as well as CK2 are highly expressed in the mammalian brain and have many bona fide substrates that are crucial in neuronal or glial homeostasis and synaptic signaling processes. The search for specific inhibitors of these enzymes has become an important challenge for the treatment of these pathologies. The role of these kinases in the molecular biology of different neurodegenerative diseases together with different natural and synthetic substances that are able to inhibit CK1, TTBK, and CK2 are discussed in this review.